(untitled) (Al-Academy, 2017)
Design system often generated relationship within the frame work of their concept of interior design a system or more can be created between design relationships within this concept in the structure of its internal space product. Through the division of all to it parts to reveal the hidden places and stages of composition and their relationship and interdependence between them. And then re- composition of all its parts, doth in the deign process at the initial stages or in the processes of treatments that are necessary after the completion of design and circulation. To be able to use other events close to the first events designed for them. In terms of idea logical in fluency and its social, economic, cultural and political dimension. As well as the surrounding environmental environment, which imposes a system of distribution of these spaces and their shape and size and then determine the pieces of pieces of furniture to the smallest detail. And the extent of the impact of these molecules in the college and absorption of the latter and the type of those particles which makes it adapted to the variables of development and regeneration within the limits of its structure according to time and place variables. Therefore, the researcher chose to select title of his research which is marked by ((the ideological effect in the in Interior space structure)). It is interested in studying the structure of the central courtyard in the old Damascus – Arab house. Which is witnessing today a shift in its functional structure by tourism investment in the city. Accordingly the study focused on four chapters, the first chapter dealt with the method logical frame work in presenting the problem which included know ledge of the ideological impact and its role in the functional. Transformation of the inner courtyard ,and its role in preserving its original heritage from the die appearing with the help of structure system of designs , and its importance and objectives and limits and then define the terms used in the research and definition. The second chapter included the theoretical framework dealing with the structure and relations in the concept of internal and relations in the particle of the college space from the particles of the roots of the review of the historical roots of the references of the central system which is characterized by the internal courtyard as well as the ideological impact in the transformation and carrier of the. old Damascus house for other events. In this chapter a set of indicators was adopted which was adopted in the analysis process for the field research procedures. The third chapter included the research procedures in terms of methodology. The descriptive approach was adopted in the case study for the analysis of the sample and the research society represented by the old Damascus houses and its intentional sample . The three axes then describe the sample and analysis it.